Barrier properties for short-fiber-reinforced epoxy foams - Alonso, M. V. (2006)
The barrier properdes of short-fiber-reinforced epoxy foam are characterized and compared with unreinforced epoxy foam in terms of moisture absorption, flammability properties, and impact properties. Compression and shear properties are also included to place in perspective the mechanical behavior of these materials. Compared with conventional epoxy foam, foam reinforced with aramid fibers exhibits higher moisture absorption and lower diffusion, while glass-fiber-reinforced foam is significantly suffer and stronger. In addition, the polymeric foam composites studied present superior fire-resistance compared with conventional epoxy foam systems.